Reviewing the Utility of Two Species in General Toxicology Related to Drug Development. (March 2018) - Prior, Helen; Baldrick, Paul; de Haan, Lolke; Downes, Noel; Jones, Keith; Mortimer-Cassen, Elisabeth; Kimber, Ian
As part of the safety assessment of new drugs, the use of two species (a rodent and a nonrodent) for regulatory toxicology studies is the typical approach taken for small molecules. For biologics, species selection is dictated by pharmacological relevance, and single species toxicology packages (typically using the nonhuman primate) are common. The UK National Centre for the Replacement, Refinement, and Reduction of Animals in Research and the Association of the British Pharmaceutical Industry are collaborating on a project to review the utility of two species in regulatory toxicology studies, with the aim to explore whether there are wider circumstances when data from a single species could be sufficient to enable safe progression in humans. An international working group consisting of 37 representatives from pharmaceutical and biotechnology companies, contract research organizations, academia, and regulatory bodies is coordinating a large-scale data sharing exercise to examine the potential for changes in current practice to reduce the number of species used for nonclinical safety testing at different stages of development. The challenge will be to determine whether two species toxicology adds significant value or whether in some instances data from a single species are sufficient (across a broader range of molecules than is currently the case) without compromising human safety.